EFFECTIVENESS FOR COMBATING SUGAR CANE DRIL - Gomes, Jéssica de Assis; Oliveira, André Luiz (Revista Interface Tecnológica, 2020)
The objective of this article is to demonstrate how the sugarcane drill acts in sugarcane, also addressing as its natural enemy the Cotesia flavipes fights this plague. Bibliographical research has presented how the natural method is effective in combating the sugarcane pest, its benefits, and the importance of this method for the environment, given that the country is marked by a strong presence of agrochemicals in the agribusiness sector. It has also been described how it was introduced in Brazil, the history of biological control and its growth over time. The research also contemplated the importance of sugarcane for the country's economy and the reason why biological control of the sugarcane drill has grown on a large scale in the country, going through topics such as the harmfulness of agrochemicals to human health, as well as the damage caused by contamination of various ecosystems, especially soils and rivers. Finally, the study demonstrated how the control and production of the sugarcane borer and the Cotesia flavipes is done in an entomology laboratory, from the identification of its cycles and the way the wasp is released in the field.